Effect of Multiaxial Testing on Polymeric Foams Performance for Shear-Compressive Loading - M. R. M., Rejab; M. M., Rahman; K., Kadirgama; M. M., Noor (2008)
Polymeric foams are widely used as core materials in sandwich structures. The polymeric foams have complex geometry shapes with various density but good as energy absorption devices. The industry has continually developed new type of polymeric foams with have different types of mechanical properties. For this purpose, a standard testing method is required to evaluate the mechanical properties of foams. The basic testing methods are uniaxial tension, compression and shear tests. The purpose of this paper is to develop the multiaxial test method as well as to contrast with the current test method. A multiaxial test rig was designed and fabricated in the project. The forces are applied to the core in form of compressive and shear. The acquired results for the multiaxial test found that the mechanical properties are slightly varied with the basic test methods. The surface failure of foams where more clear failure surface locus is also investigated.